Crisis Management in Communication: A Study on MH370, MH17 and QZ8501 Aviation Tragedies - MOHD NAZRI, LATIFF AZMI; Mohd Fauzi, Abdul Hamid; Zulazhan, Ab. Halim (2016)
In 2014, the MH370, MH17 and QZ8501 flight crash tragedies become a viral issue and attract the attentions of media and stakeholders, globally, and raise many crises to the airlines companies, respectively, including the risk of losing their stakeholders' trust. The study is to identify the crises management approaches used for the tragedies related, to analyse and compare the effectiveness of the crises management between two well-known airlines companies, Air Asia and Malaysia Airlines (MAS). Qualitative method was used to collect the data related to the ways that the airlines company had taken to handling the crises. So, the researchers conducted content analysis by studying the secondary data, due to the fact of the airlines reluctance to give out information about safety procedures or policies, as the airlines accidents are a very sensitive subject. The data are mostly of the documentary types in written format of press conferences, press releases and media coverage of the accidents by local and western daily press (printed and online news).